PEMANFAATAN MEDIA ANIMASI DALAM MENGASAH KEMAMPUAN SISWA UNTUK MEMAHAMI MATERI BENTUK SUKU DAN BUDAYA DI MIN 4 BIMA - Trimansyah Trimansyah (Prodi PAI STIT Sunan Giri Bima, 2024)
This study aims to determine the use of animation media in improving students' understanding of the Arts and Crafts (SBDP) subject, covering ethnic and cultural forms. The problem faced is low interest and motivation in learning due to the dominance of lecture methods and printed books. The study used a descriptive qualitative approach through observation, interviews, and documentation. The results show that animation media in the form of videos, images, and sounds are able to create an interesting learning atmosphere, foster motivation, and improve student understanding. Success is supported by the availability of facilities such as LCDs, laptops, and electronic devices, while the main obstacles are technical problems such as power outages and teachers' limited mastery of technology. Thus, animation media is proven to be more effective than conventional methods and has the potential to improve student learning outcomes.